Systems of producing hydrogen and biochar from biomass assisted by iron and steel slag extract - Zhao, Huangjing; Zhou, Xiaozhou (2025)
Systems of producing hydrogen and biochar from biomass assisted by iron and steel slag extract include: a pretreatment system that the reactants, including the biomass, iron-based catalyst and alkaline reagent, are pretreated and fully mixed at specific ratios in the pretreatment system; thermal reactor that the mixed reactants from the pretreatment device are transferred into and fully reacted in the thermal reactor; a solid residue collector that the solid residue is collected by the solid residue collector at the discharge outlet of the thermal reactor after the reacted mixture is separated; a gas collection system that he generated hydrogen-based gas is collected by the gas collection system from the exhaust port of the thermal reactor.